2021
DOI: 10.1371/journal.pone.0243093
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the PTENP1 pseudogene as potential epigenetic marker of age-related changes in human endometrium

Abstract: The processed pseudogene PTENP1 is involved in the regulation of the expression of the PTEN and acts as a tumor suppressor in many types of malignances. In our previous study we showed that PTENP1 methylation is present not only in tumor, but also in normal endometrium tissues of women over 45 years old. Here we used methylation-specific PCR to analyze methylation status of CpG island located near promoter region of PTENP1 in malignant and non-malignant endometrium tissues collected from 236 women of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…In particular, the expression of the VDAC1P8 pseudogene undergoes no or little variation and is presumably under the transcriptional control of adjacent genes, as observed with other pseudogenes (i.e. LIN28 and PTEN ) (33,63,64). Indeed, five other genes located at the 6q24.2 locus and controlled by the same regulatory elements acting on VDAC1P8 correlate with AML.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In particular, the expression of the VDAC1P8 pseudogene undergoes no or little variation and is presumably under the transcriptional control of adjacent genes, as observed with other pseudogenes (i.e. LIN28 and PTEN ) (33,63,64). Indeed, five other genes located at the 6q24.2 locus and controlled by the same regulatory elements acting on VDAC1P8 correlate with AML.…”
Section: Discussionmentioning
confidence: 80%
“…It is also important to note that previous studies have shown the existence of different DNA methylation rates for pseudogenes and their parent genes (33,63,64).To better understand the significance of VDAC1 pseudogenes activation patterns in relation to parent gene expression levels, we focused our attention on the DNA methylation status of these pseudogenes and VDAC1 gene. Exactly, we observed that the methylation levels of the VDAC pseudogenes presumably depended on their position within the genome.…”
Section: Discussionmentioning
confidence: 99%
“…There are results about the influence of aging on the human uterine tissue. The observed finding suggests that uterine aging impairs the function of the uterine myometrium [ 11 , 12 , 13 ], neurofibers of the human uterus [ 14 ], and human endometrium [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, considering the higher methylation of PTENP1 in older women and its tumor-suppressive role, it has been suggested that PTENP1 methylation is associated with subsequent elevation of its expression. It may also be a protective mechanism against the malignant transformation of endometrial tissue in older women [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, PTENP1, the first identified pseudogene, was reported to be down-regulated in numerous cancers including breast cancer, melanoma, and endometrioid endometrial carcinoma (Chen et al, 2018;Gao et al, 2019;Poliseno et al, 2011). Besides, methylation of the PTENP1 as potential epigenetic marker was associated with a more favorable prognosis for endometrial cancer (Kovalenko et al, 2021). Epigenetic modifications have been reported to be widely involved in the development of ovarian cancer and can be used as a potential biomarker as well as a therapeutic target for the disease Rattanapan et al, 2018;Singh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%